Promoting Mental Health in Healthcare Workers in Hospitals Through Psychological Group Support With Eye Movement Desensitization and Reprocessing During COVID-19 Pandemic: An Observational Study - Fogliato, Elisa; Invernizzi, Roberta; Maslovaric, Giada; Fernandez, Isabel; Rigamonti, Vittorio; Lora, Antonio; Frisone, Enrico; Pagani, Marco (Frontiers in Psychology, 2022)
Background. Psychosocial support was provided by EMDR-IGTP within the hospitals in the Northern Italy in favor of healthcare workers during tha COVI-19 pandemic. This study aimed at evaluating the effectiveness of treatment in terms of a) symptomatology reduction related to peri- and posttraumatic stress; b) clinical improvement over time; c) maintenance of the achieved outcome over time. Methods. The population was composed by healthcare workers who spontaneously requested psychological intervention both in the first and in the second emergency wave. Statistical analyses were carrie out to highlight the differences in Impact of Event Revisedf (IES-R) and Post-Traumaric Growth Inventory before and after the group intervention. Results. In both the first and second wave, pre-treatment values are higher than post-treatment values for all dimensions of the IES-R. The results show that there are no significant differences between the first and second waves with regard to the treatment effect. The healthcare workers maintained the positive changes over time despite the prolonged exposure to the emergency and the possibility of retraumatization at the onset of a new emergency phase, irrespectively for the working place. They showed less vulnerablility and more resilience than health care workers not treated in the first wave. The scores of the pre-treatment variables of halthcare workers affected by COVID-19 were higher than those in the second wave. Conclusions. The COVID-19 had a significant impact on the well-being of healthcare workers who worked in hospitals. Psychological support in emergency is needed.